2017
DOI: 10.1111/irv.12450
|View full text |Cite
|
Sign up to set email alerts
|

Single radial haemolysis compared to haemagglutinin inhibition and microneutralization as a correlate of protection against influenza A H3N2 in children and adolescents

Abstract: BackgroundSerum antibodies are often used as correlates of protection for influenza. Three commonly used serological assays for detecting influenza‐specific serum antibodies are single radial haemolysis (SRH), haemagglutinin inhibition (HAI) and microneutralization (MN). However, here are limited data on SRH as well as HAI and MN as correlates of protection against influenza in children and adolescents. There are also limited data that compare SRH to HAI and MN.ObjectivesWe sought primarily to understand how S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
19
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 17 publications
4
19
1
Order By: Relevance
“…Previous studies involving A strains support the strong agreement between HI and SRH assays found in present study . The correlation between SRH and MN assays observed in this study is in agreement with the findings of the previous studies that used equine influenza strains and H3N2 influenza strain . However, unlike Wang et al , who found much higher correlations between SRH and MN assays than between SRH‐HI and HI‐MN assays, we found no significant differences among them.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Previous studies involving A strains support the strong agreement between HI and SRH assays found in present study . The correlation between SRH and MN assays observed in this study is in agreement with the findings of the previous studies that used equine influenza strains and H3N2 influenza strain . However, unlike Wang et al , who found much higher correlations between SRH and MN assays than between SRH‐HI and HI‐MN assays, we found no significant differences among them.…”
Section: Discussionsupporting
confidence: 92%
“…The data highlight strong correlations between HI, MN, and SRH assays for influenza A strains (H1N1 and H3N2). A significant correlation between HI and MN has been found by Veguilla et al with the same H1N1 strain used in this study, and, in other studies, with different influenza strains, such as A/Brisbane/10/2007 (H3N2), A/Brisbane/59/2007 (H1N1), and equine influenza viruses . Previous studies involving A strains support the strong agreement between HI and SRH assays found in present study .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations